Evaluation of the APEC environmental goods initiative: A dominant supplier approach - George Manzano; Shanti Aubren Prado (Philippine Institute for Development Studies (PIDS), 2015)
The paper evaluates the feasibility of sectoral liberalization of environmental goods for the Asia-Pacific Economic Cooperation (APEC). Using the model originally developed by Wonnacott, it argues for the liberalization of goods predominantly supplied by APEC members, thereby minimizing the free rider problem that usually afflicts most favored nation liberalization. The paper then ranks the different items in the APEC list of environmental goods according to economic advisability, given the predominant supplier framework. It thus demonstrates the economic rationale why APEC, as a whole, should consider liberalizing a number of environmental goods. The paper also examines the distributional impact of the proposed scheme on the individual members, particularly on the trade interest of the Philippines.
Keywords: 330; Philippines; Asia-Pacific Economic Cooperation (APEC); environmental goods; services; tariff; trade liberalization